Innovation Orientation, Self-Motivation, and Marketing Communication: Their Role in Supporting the Marketing Performance of Women Entrepreneurs in Micro, Small, and Medium Enterprises - Adelia Adelia; Rahmad Solling Hamid; Sofyan Syamsuddin; Muhammad Ikbal (Proceedings Series on Social Sciences & Humanities, 2024)
Background: The marketing landscape in the context of micro, small, and medium enterprises (MSMEs) has witnessed profound transformations driven by innovation, self-motivation, and marketing communication strategies. Understanding the intricate interplay of these factors is essential to empowering and uplifting women entrepreneurs within this sector, fostering their marketing success and economic contributions. This study aims to examine the relationship between innovation orientation, self-motivation, marketing communication, and marketing performance among women entrepreneurs. Method: The empirical analysis was conducted using a sample of 130 women entrepreneurs in micro, small, and medium enterprises. This study used an online survey for data collection. After passing reliability and validity tests, the data were analyzed with partial least squares structural equation modeling. Results: The research results indicate that innovation orientation has a significant positive direct influence on marketing communication. Innovation orientation also has a significant direct positive influence on marketing performance. Furthermore, self-motivation has a significant positive direct influence on marketing performance. Finally, self-motivation also has a significant positive influence on marketing performance. Conclusion: This study illuminates the pivotal roles of innovation orientation, self-motivation, and marketing communication in bolstering the marketing performance of women entrepreneurs in micro, small, and medium enterprises (MSMEs). The findings underscore the multifaceted nature of these influences, emphasizing the need for tailored strategies and support mechanisms to empower women entrepreneurs in their marketing endeavors, ultimately contributing to the growth and sustainability of MSMEs.